Balancing productivity and carbon emissions: the potential for carbon reduction in wheat fertilization practices in China - Qi, Li; Li, Yanan (Frontiers in Environmental Science, 2024)
The irrational application of chemical fertilizers in wheat cultivation not only threatens the agricultural ecosystem but also significantly contributes to carbon emissions, impeding the achievement of "carbon peaking" and "carbon neutrality" goals. The objective of this research is to assess the efficiency of chemical fertilizer use in wheat production across ten major wheat-producing provinces in China from 2004 to 2020. We employed a stochastic frontier production function to evaluate the technical efficiency of fertilizer use, determining feasible reduction levels. The Gini coefficient, kernel density estimation, and Markov chain analysis were further utilized to dissect the spatio-temporal dynamics of carbon emission reduction potential. Our findings provide a detailed analysis of the carbon emission reduction potential in wheat chemical fertilizer use across China's ten major wheat-producing provinces from 2004 to 2020. The average carbon emission reduction potential is significant, at 251.1 kg CE/hm ² , with considerable variation observed among regions.The western region, in particular, stands out with the highest potential, reaching up to 336.51 kg CE/hm², which is notably higher compared to the eastern (230.05 kg CE/hm²) and central regions (158.28 kg CE/hm ² ). The spatial distribution of this potential is uneven, and the disparities are progressively increasing, primarily due to inter-regional differences. Despite a general decline in carbon reduction potential, the spatial distribution remains relatively consistent. To foster sustainable wheat production, it is imperative to prioritize the western region for targeted chemical fertilizer carbon reduction initiatives. Attention must also be given to the issue of regional disparities in lowcarbon wheat production. Enhancing the role of soil testing and fertilizer recommendations is essential to increase the effectiveness of carbon reduction efforts. Additionally, a multi-faceted approach that incorporates various alternative measures is necessary to drive further reductions in chemical fertilizer-related carbon emissions.